THE IMPLEMENTATION OF JOB CREATION LAW NO. 11 2020 ON THE EASE OF BUSINESS: (THE ANALYSIS OF OPPORTUNITIES AND THREATS USING THE EDWARDS III MODEL APPROACH) - M Afif Hasbullah; Nisaul Barokati Seliro Wangi (STIE Mahardhika, 2021)
The investment procedure in Indonesia is still seen as complex and complicated. The complexity is seen in licensing, land acquisition, taxation, and other investment-related issues. A policy or regulation is required to simplify and accelerate the investment procedure. The existence of the Omnibus law No. 11 of 2021 on Job Creation is expected to make investing in Indonesia easier. However, the case with policies and regulations in general, good regulations are not always well-implemented. As a result, the Edwards III Model approach should be used to examine the execution of Law No. 11 of 2020 about Job Creation Related to the Ease of Business Cluster. The analysis's results showed that four elements will influence the success as well as potential dangers associated with the law's policy implementation, including communication factors, resource considerations, implementer attitude factors, and bureaucratic structure factors.